The Mathematical Critical Thinking of MTs Students in Solving Math Problems - Anike Putri (Journal of Research on Mathematics Instruction (JRMI), 2020)
The purpose of this descriptive qualitative research was to provide a description of the mathematical critical thinking skills of MTs students in solving mathematical problems, more precisely in the context of a flat side room shape. The research subjects were selected based on the UTS Math score. Subjects who were Grade VIII students of the Riau Technology Islamic Boarding School were grouped into high, medium, and low mathematical abilities. From each group, one student who has good communication skills is chosen as the research subject. After giving tests and interviews to the three subjects, the results obtained showed that the average test for each indicator of mathematical critical thinking skills at the inference stage reached 96.83, the analysis stage reached 88.33, the evaluation stage reached 79.33 and the inference stage reached 59.83. Each subject has different critical thinking skills according to the indicators of mathematical critical thinking skills